PERAMALAN PENJUALAN DENGAN METODE EXPONENTIAL SMOOTHING DAN METODE LEAST SQUARE GUNA MENGOPTIMALKAN PENJUALAN PRODUK NUGGET MAILA SARI DESA BANJARAN, KECAMATAN SALEM, KABUPATEN BREBES - Dwi Ika Pebri Sentika; Ayus ahmad Yusuf; Robi Awaludin (LP2M Universitas Bina Bangsa, 2021)
Maila Sari Brebes Nugget Company is one of the companies engaged in the food industry, in that its sales of Nugget products have a fluctuating volume of sales each month due to the lack of application of scientific forecasting planning methods, so forecasting techniques need to be applied by the company. This study aims to optimize the sales plan of Maila Sari Brebes Nugget, do the calculation between the Exponential Smoothing method and the Least Square method of the error value, can be used as an appropriate and effective method in accordance with the real sales data of Maila Sari Brebes. Using the Microsoft Excel 2010 application and POM-QM for Windows 5. Based on the results of the analysis that has been done that the Exponential Smoothing method α = 0.9 has a smaller difference with an average difference of 508.892833 and an average forecast error rate of 3.44% per month, compared to the Least Square method which has an average difference of 6064,772 and an average error rate of forecasters of 41.67% per month